Identidad Subjetiva Y Derechos Humanos En Mujeres Afrocolombianas Del Departamento De Nariño, Residentes En Bogota, Victimas Del Desplazamiento Forzado Por El Conflicto Armado. (2019)
The present investigation analyzes the transformation of the identity in Afro-descendant women, the relationships of the armed conflict and the forced displacement, together with the human right and how it becomes effective for these women, the relationship between human rights, displacement and subjective identity, the establishment of the root of the displacement arose a change in the subjective identity and the same time in which we contribute in human rights to respond. Semi-structured interview with five women living in the locality 4 of San Cristóbal Sur, in Bogotá, who have been assisted in the armed conflict and the forced role, the academic objectives of the project have been explored, then in each of the homes to collect the information by means of the questions that were: How does it work? How does it work? How does it work? How does it work? How does it work? in its family structure and the social processes that frame the subjective identity.